ANALISIS KEPUASAN KERJA TERHADAP FASILITAS KERJA GUNA MENINGKATKAN PRODUKSI - Rifki Ma’mun, Moh; Milana, Lia (Universitas Majalengka, 2019)
PT Sinjaraga Santika Sport is an internasional phased sporting goods manufacturer in the loading of the ball industry with 60 wmployees, the researcher aims to analyze job satisfaction with work facilities in the company and the influence felt by workers when they do not feel by job satisfaction. The method used this study is SPSS 21 which processes data from the result of a questionnaire with a sample of all employees totaling 60 employees. Analysis of the data used in this study is a test of validity and reliability. The result of the study show that the validity test is declared valid because the rcount is greater thanrtable. Reliability tests show reliability because cronbach alpha is greater than 0.60. From the result of respondent’s answer in job satisfaction categorized as high namely 1,497 work facilities are categorized as high, namely 1,235 and increasing production is categorized as high, namely 909.